2021
DOI: 10.1136/tsaco-2021-000679
|View full text |Cite
|
Sign up to set email alerts
|

Emergency general surgery utilization and disparities during COVID-19: an interrupted time-series analysis

Abstract: ObjectiveWe aimed to compare general surgery emergency (GSE) volume, demographics and disease severity before and during COVID-19.BackgroundPresentations to the emergency department (ED) for GSEs fell during the early COVID-19 pandemic. Barriers to accessing care may be heightened, especially for vulnerable populations, and patients delaying care raises public health concerns.MethodsWe included adult patients with ED presentations for potential GSEs at a single quaternary-care hospital from January 2018 to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…On the other hand, although emergency surgical volume similarly decreased, it has continued to decrease during the post-COVID period. This finding may be consistent with those in other studies where hospitals worldwide that experienced decreases in emergent surgeries during the pandemic [ 32 37 ]. Again, we believe this may be due to sicker patients avoiding medical care or facing insurmountable challenges in accessing care during the pandemic, but more research is needed.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, although emergency surgical volume similarly decreased, it has continued to decrease during the post-COVID period. This finding may be consistent with those in other studies where hospitals worldwide that experienced decreases in emergent surgeries during the pandemic [ 32 37 ]. Again, we believe this may be due to sicker patients avoiding medical care or facing insurmountable challenges in accessing care during the pandemic, but more research is needed.…”
Section: Discussionsupporting
confidence: 93%
“…These are similar to findings of Dick et al who saw a 58% decrease in EGS admission but increased operative rate (19–42%), as well as increased presentation severity. 20 While several other studies saw decreased operative rates during the pandemic, 21 , 22 , 23 , 26 , 42 this study is one of the first to demonstrate a similar rate of operative EGS before and during the COVID Pandemic. Additionally, severity of presentation was similar with equivalent ED GCS, WBC, and initial lactate.…”
Section: Discussionsupporting
confidence: 52%
“…Early studies to characterize the presentation, severity, and outcomes in the surgical management of biliary disease during the pandemic have shown conflicting results. 9 , 10 , 11 While Valles et al demonstrated decreased cholecystitis admissions without increased disease severity during the pandemic, 9 another study by Murphy et al identified increases in acute calculous cholecystitis presentation. 10 …”
Section: Introductionmentioning
confidence: 99%